2019
DOI: 10.1161/circulationaha.118.036553
|View full text |Cite|
|
Sign up to set email alerts
|

Racial Differences in Sudden Cardiac Death

Abstract: Background: African Americans (AAs) have a higher incidence of out-of-hospital sudden cardiac death (SCD) compared with Whites. However, the racial differences in the cumulative risk of SCD and the reasons for these differences have not been assessed in large-scale communitybased cohorts. The objective of this study is to compare the lifetime cumulative risk of SCD among AAs and Whites, and to evaluate the risk factors that may explain racial differences in SCD risk in the general population. Methods: Cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 45 publications
(55 reference statements)
3
52
1
Order By: Relevance
“…Many previous studies recognized race as an independent and strong risk factor of SCD even after adjusting for socioeconomic factors but attributed it -at least partiallyto underlying biological differences between black and white individuals. 1,2,4 In contrast, our comprehensive study of EP substrate did not find meaningful effect modification by race. Results of our study call attention to structural racism as an important determinant of the increased SCD rate in black as compared to white individuals.…”
Section: Race Does Not Modify An Association Of Ep Substrate With Scdcontrasting
confidence: 86%
See 3 more Smart Citations
“…Many previous studies recognized race as an independent and strong risk factor of SCD even after adjusting for socioeconomic factors but attributed it -at least partiallyto underlying biological differences between black and white individuals. 1,2,4 In contrast, our comprehensive study of EP substrate did not find meaningful effect modification by race. Results of our study call attention to structural racism as an important determinant of the increased SCD rate in black as compared to white individuals.…”
Section: Race Does Not Modify An Association Of Ep Substrate With Scdcontrasting
confidence: 86%
“…Based on a recent study demonstrating a significantly stronger association of hypertension with SCD in black as compared to white individuals, 1 we additionally constructed a set of models that included interaction with both race and hypertension categories. The white hypertension-free subgroup was the reference.…”
Section: Survival Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 In addition, it was shown that black and African American individuals are at increased risk of sudden cardiac death compared to white individuals. 37 Because of these differences, it may be early to assume that diabetes medications that improve cardiovascular benefit in white patients would produce similar results in black patients. Given this concern, and the high burden of cardiovascular disease in black and African American patients, with or without diabetes, it is crucial to evaluate diabetes regimens that would reduce such major complications and might lessen the racial disparities that persist in cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%